The effect of azomite as soil amendment on the growth performance of paddy / Ilham Hareth Mohd Rapino - Mohd Rapino, Ilham Hareth (Faculty of Plantation and Agrotechnology, 2014)
An experiment was done on February until June 2014 at UiTM Perlis. The study was conducted to evaluate the soil amendment and growth performance of rice (Oryza sativa L.) on different amount of azomite. Five treatments with four replication were prepared for laboratory and field experiment respectively. The five treatments were treatment 0 as a control treatment (0 g of azomite), treatment 1 (1 g of azomite), treatment 2 (2 g of azomite), treatment 3 (3 g of azomite), and treatment 4 (4 g of azomite). The amount was applied for each polybag. The experiment was done in a Completely Randomized Design (CRD). MR220 variety of rice and azomite was used in this study. All parameters of these experiment were measured in order to be compared statistically using ANOVA with Tukey analysis. Based on the result, azomite had enhances growth performance and soil amendment of rice. However, the study indicates that the azomite had certain rate in order to reach optimum growth development. Optimum growth was found at 2 g of azomite. When more and less than 2 g of azomite applied during to the experiment, the negative effect was shown on the growth of rice.